Chlamydia trachomatis remodels stable microtubules to coordinate Golgi stack recruitment to the chlamydial inclusion surface. Issue 6 (3rd November 2014) - Al‐Zeer, Munir A.; Al‐Younes, Hesham M.; Kerr, Markus; Abu‐Lubad, Mohammad; Gonzalez, Erik; Brinkmann, Volker; Meyer, Thomas F.
Summary C hlamydia trachomatis (Ctr), an obligate intracellular bacterium, survives and replicates within a membrane‐bound vacuole, termed the inclusion, which intercepts host exocytic pathways to acquire nutrients. Ctr subverts cellular trafficking pathways from the Golgi by targeting small GTPases, including Rab proteins, to sustain intracellular bacterial replication; however, the precise mechanisms involved remain incompletely understood. Here, we show that Chlamydia infection in human epithelial cells induces microtubule remodeling, in particular the formation of detyrosinated stable MTs, to recruit Golgi ministacks, but not recycling endosomes, to the inclusion. These stable microtubules show increased resistance to chemically induced depolymerization, and their selective depletion results in reduced bacterial infectivity. Rab6 knockdown reversibly prevented not only Golgi ministack formation but also detyrosinated microtubule association with the inclusion. Our data demonstrate that Chlamydia co‐opts the function of stable microtubules to support its development.